2007
DOI: 10.1111/j.1365-2133.2007.08057.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumour-infiltrating CD4+CD25+FOXP3+ regulatory T cells in human cutaneous benign and atypical naevi, melanomas and melanoma metastases

Abstract: The strong prevalence of CD25+FOXP3+ Tregs both in junctional and compound atypical naevi and radial growth phase melanomas, suggests that they induce immunotolerance early during melanoma genesis, favouring melanoma growth. Their evaluation within a tumour site could be useful for prognostic and therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
(106 reference statements)
0
44
1
Order By: Relevance
“…We did not make attempts to characterize the labeled cell type(s) more precisely by double immunohistochemical staining. Although the expression of FOXP3 could be induced in vitro in CD4 + CD25 − and CD8 + lymphocytes as well [26][27][28][29], in previous immunohistochemical studies on melanoma all FOXP3 + cells expressed CD3 and almost all of them CD4 and CD25 as well [18,19], suggesting that the vast majority of tumor-infiltrating FOXP3 + cells are CD4 + CD25 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We did not make attempts to characterize the labeled cell type(s) more precisely by double immunohistochemical staining. Although the expression of FOXP3 could be induced in vitro in CD4 + CD25 − and CD8 + lymphocytes as well [26][27][28][29], in previous immunohistochemical studies on melanoma all FOXP3 + cells expressed CD3 and almost all of them CD4 and CD25 as well [18,19], suggesting that the vast majority of tumor-infiltrating FOXP3 + cells are CD4 + CD25 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Mourmouras et al characterized cutaneous melanocytic lesions including melanomas with respect to the prevalence of Tregs, and found a lower percentage of Tregs in vertical than in radial growth phase melanomas [18]. Contrary to this finding, another small-scale study described higher prevalence of these cells in VGP compared to RGP, and also in stage III-IV tumors compared to stage I ones [19].…”
Section: Introductionmentioning
confidence: 95%
“…+ cells have been considered to represent Tregs in previous reports [20,21], we analysed the prevalence of CD25…”
Section: Foxp3mentioning
confidence: 99%
“…However, clinical studies (11,13) (17,18). Certain studies have identified increased peripheral Treg levels in patients with metastatic MM (19)(20)(21)(22)(23); therefore, therapies that decrease Treg levels may be beneficial for these patients.…”
Section: Introductionmentioning
confidence: 99%